Antibacterial metals and alloys for potential biomedical implants - Zhang, Erlin (Bioact Mater, 2021)
Metals and alloys, including stainless steel, titanium and its alloys, cobalt alloys, and other metals and alloys have been widely used clinically as implant materials, but implant-related infection or inflammation is still one of the main causes of implantation failure. The bacterial infection or inflammation that seriously threatens human health has already become a worldwide complaint. Antibacterial metals and alloys recently have attracted wide attention for their long-term stable antibacterial ability, good mechanical properties and good biocompatibility in vitro and in vivo. In this review, common antibacterial alloying elements, antibacterial standards and testing methods were introduced. Recent developments in the design and manufacturing of antibacterial metal alloys containing various antibacterial agents were described in detail, including antibacterial stainless steel, antibacterial titanium alloy, antibacterial zinc and alloy, antibacterial magnesium and alloy, antibacterial cobalt alloy, and other antibacterial metals and alloys. Researches on the antibacterial properties, mechanical properties, corrosion resistance and biocompatibility of antibacterial metals and alloys have been summarized in detail for the first time. It is hoped that this review could help researchers understand the development of antibacterial alloys in a timely manner, thereby could promote the development of antibacterial metal alloys and the clinical application.